Targeting steroid receptor coactivators in cancer via small molecule agents - Gilad, Yosi; Shimon, Ortal; Lonard, David M.; O’Malley, Bert W. (Frontiers in Drug Discovery, 2024)
Steroid receptor coactivators (SRCs) are a family of nuclear receptor (NR) coregulators comprised of three evolutionarily related, yet distinct proteins SRC-1, SRC-2 and SRC-3. The SRCs interact with NRs and other transcription factors to regulate their transcriptional activity, impacting a wide variety of physiological and pathological processes. Abnormal expression or dysfunction of SRCs is associated with a diverse range of pathological conditions, including metabolic disorders, genetic and reproductive malfunctioning, impaired embryogenesis and most notably cancer which is the focus of this review. As key integrators of NR and growth factor signaling pathways, SRCs regulate multiple oncogenic programs, particularly in hormone-related malignancies, and thus represent attractive biological targets for cancer treatment. Here we review the evolution of the discovery process for small molecule targeting agents of SRCs and the opportunities they present for cancer therapy.